Cross Cultural Perspective towards the Realization of EFL Learners’ Request Appropriateness and Politeness - Seniarika, Seniarika (Universitas Islam Negeri Raden Intan Lampung, 2017)
Each culture has its own perspective towards speech acts. What is perceived as a formal context in one culture may be seen as informal in another. This study is intended to find out the importance of knowing cross cultural perspective towards speech acts of request produced by EFL learners. In this study the researcher used descriptive qualitative research. The researcher found that numerous studies conducted did not separate speech acts appropriateness and politeness though actually appropriateness and politeness are two different things, appropriate requests might be impolite to the interlocutor. Since maintaining conversation in cross culture communication is essential, the researcher assumes that it is kind of urgent to conduct a research regarding to request appropriateness and politeness.